The Representation of Trauma in DeLillo's Falling Man: A Postmodernist Reading - Amghar Rachida; Belhammou Khedidja (University of El-Oued جامعة الوادي, 2025)
Abstract This dissertation examines the representation of trauma in Don DeLillo's Falling Man (2007) through the lens of postmodernist narrative techniques. Focusing on the psychological and cultural effect of the 9/11 attacks, the study examines how DeLillo's fragmented narrative, insecure narration, and intertextual references mirror the disorienting nature of traumatic memory. Referring trauma theory and postmodern literary theory, the analysis identifies how the novel subverts traditional trauma narratives through resistance to linear development and closure. At the heart of the research is the main character, Keith Neudecker, whose disjointed experiences are symbolic of society's collective failure to cope with collective trauma. The dissertation also analyzes how the novel's stylistic ambiguity attests to the unimaginable quality of trauma. By situating The Falling Man among post-9/11 fiction and postmodernism, this study demonstrates how DeLillo's innovative style serves justice to the fracture in American identity. The research is decisive in affirming that the novel not only represents trauma but also shows the shortcomings of language in expressing its full impact, making a substantial contribution to debates on trauma fiction and postmodern aesthetics. Keywords: Collective Trauma, Postmodernism, Falling Man, Trauma, ,9/11 الملخص تناقش هذه الأطروحة تمثيل الصدمة في رواية دون ديليلو الرجل الساقط (2007)، وذلك عبر تقنيات السرد ما بعد الحداثية، مع التركيزعلى الأثر النفسي والثقافي لحادثة 11 سبتمبر. يدرس البحث كيفية تصوير السرد التجزيئي، والرواية غير المستقرة، والإحالات التناصية في عمل ديليلو الطبيعة المشتتة للذاكرة الصادمة. باعتبار نظرية الصدمة والنظرية الأدبية لما بعد الحداثة كأساس، يحلل البحث كيفية تقويض الرواية للسرديات التقليدية للصدمة عبر رفض التطور الخطي والحلول المغلقة. إذ تمحور ذلك عبر دراسة الشخصية الرئيسية؛ كيث نوديكر، التي تعكس تجاربها المفككة عجز المجتمع الجماعي عن مواجهة الصدمة من ذات النوع؛ أي الجمعية. كما تفحص الأطروحة شهود غموض الأسلوب في الرواية على طبيعة الصدمة التي يُمتنع تخيلها. بوضع الرجل الساقط ضمن سياق أدب ما بعد 11 سبتمبر وما بعد الحداثة، تُبين هذه الدراسة على أن أسلوب ديليلو الابتكاري يمثل بصدق انكسار الهوية الأمريكية. يخلص البحث إلى أن الرواية لا تُصوّر الصدمة فحسب، بل تكشف أيضاً عن قصور اللغة في التعبير عن تأثيرها الكامل، مساهمةً بذلك إسهاماً مهماً في النقاشات حول أدب الصدمة وجماليات ما بعد الحداثة.
Master's Degree In Literature and Civilization
Keywords: الصدمة الجماعية، ما بعد الحداثة، الرجل الساقط، الصدمة، 11 سبتمبر: Collective Trauma; Postmodernism; Falling Man; Trauma; 9/11